ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENDATAAN KELUARGA PENERIMA MANFAAT (KPM) BANTUAN PANGAN NON TUNAI (BPNT) PADA DINAS SOSIAL KOTA JAMBI - Rahmadani, M. Irsyad; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2019)
The Social Service Office of Jambi City faces difficulties in registering the people who receiving non-cashfood assistance. Data collection is still done conventionally so that it allows errors in the process of datainput, multiple identities, files build up, sometimes files are easily lost and difficult to find. This problemcauses the author to provide a solution in the form of a website-based KPM BPNT Data InformationSystem using Use Case Diagrams, Activity Diagrams and Class Diagrams as a system design model. Thedesign of the system is only limited to a prototype. The results obtained in the form of a Draft InformationSystem for KPM BPNT Information for Jambi City Social Service Office which can be implementedfurther so as to produce a data information system that supports the data collection activities of the JambiCity Social Service Ofice